Final answer:
To solve the equation x/4 + y/3 = 1 for x, subtract y/3 from both sides, multiply through by 4 to eliminate the fraction, and finally distribute the 4 to get x in terms of y as x = 4 - (4y/3).
Step-by-step explanation:
To solve the equation x/4 + y/3 = 1 for x, first we will isolate x on one side of the equation.
Begin by subtracting y/3 from both sides of the equation: x/4 = 1 - y/3.
To eliminate the fraction, multiply both sides by 4, the denominator of x, which gives: x = 4(1 - y/3).
Finally, distribute the 4 into the parentheses to simplify the equation: x = 4 - (4y/3).
The equation for x in terms of y is therefore: x = 4 - (4y/3).